Business strategy for pt. Garuda indonesia tbk. Base on operation and finance ratio performance period 2011-2015 - Mangiring Ganda Parulian Butar Butar, Paul; Hamsal, Mohammad (The Indonesian Journal of Business Administration, 2016)
Abstract: In 2011-2015, PT Garuda Indonesia, experienced lots of challenges started from the increment of aviation fuel which increase to the end of 2014, depreciation of rupiah and unexpected economic growth. Those three things caused PT Garuda Indonesia Tbk suffered a loss and reached the peak losses in 2014 at the amount of US$ (371.974.942). As the condition described above, the operating performance of work and financial ratios in the period 2011-2015 should be analyzed performance of financial ratios covering liquidity, activity, solvency and profitability while operation performance is analyzed by using PESTEL Model , The Five Forces Model, 4P and VRIO and then reanalyzed by using SWOT analysis / TOWS, afterward do differentiation strategy and the value proposition alignment. The result of analysis found that the loans of PT Garuda indonesia Tbk exceeded its assets, that all activities done by this company were financed by the loans; work process that are not well integrated; a constant ASK though the airplane annually increases; competitors dominate domestic market; the lack of experts for aircraft maintenance cause readiness of the airplane decreases in 2014 into 99.27 with the use of aircraft wer also getting down into 9.08 in 2014. Thus, it is recommended to PT Garuda Indonesia Tbk to develop a high performance manpower (collaborating with polytechnics and leading universities), build an flight's IT system that all units can be fully integrated and the customers can facilitate well; applying SLA (Service Level Agreement) or KPI system in all units; reviewing routes (considering the favorable and unfavorable for maintenance); postponing the plan of buying a new aircraft till ASK increased in accordance with the number of the aircraft and an innovation where Full Carrier Service has a low cost without reduce standard for comfortable and Safety so it can compete with the domestic and international competitor. It can be seen from the relation between cost, volume, and price that PT Garuda Indonesia should do a business strategy with affordable prices for the customers can feel a prestige, safety, and comfort flight. Therefore, Garuda Indonesia flight will always be in demand and it will increase the ASK. Thus, the price will decrease and the margin will arise significantly. Keywords: Financial Ratio, CVP, ASK, Uniqueness, FSC with Affordable Price